'Nine times the space' : from translator's notes to Milton's Paradise lost - Marjan Strojan (Acta Neophilologica, 1997)
Understanding the original meaning in the original context forms the basis of any translation. Translating poetry, however, requires an understanding which goes some way beyond the formal requirements of intelligent reading and informed interpretation. There are mental processes in any reading which are not easy to define in cognitive terms. Reading poetry, however, is by definition an aesthetic process, having a lot in common with our listening of music or looking at a work of art, where our cognitive functions are trained to be neither the exclusive interpreter of the subject nor the supreme selector of thought. Now, there are perhaps passages in Lacan or Nietzsche or Marx which can be enjoyed in synaesthetic terms as well as there are lines and sometimes whole paragraphs in Paradise Lost where little or no visual or musical perceptions are required beyond those usually· attached to any piece of theological meandering. But our perception of them is predetermined by the specific difference, inherent in the text, which relates not only to the difference of style, but also to the difference in our reading of them.